Education of Children with Disabilities Using ICT (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The use of ICT in a correctional school in teaching students should be oriented towards the main activity of children - the game, therefore, the tasks should be entertaining, game-like, and correspond to intellectual abilities and age needs. The specifics of the teacher's work require an individual approach to each child. Therefore, the teacher is constantly looking for new methods and teaching methods, because they are different for each child. Knowledge of defectology and psychology helps to correctly determine the forms and methods of the lesson depending on the child's condition.